Analisis Struktur Kolom dan Balok Pada Perencanaan Gedung Fakultas Universitas Sains Cut Nyak Dhien - T. Ramadhani; Yuslinda; Rajib Muammar (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2026)
The Faculty of Engineering lecture building used in the planning and preparation of the final project is located at Jln. Perumnas No.45 Paya Bujok Seuleumak, Langsa Baro, Langsa City, Aceh, is included in risk category IV because it is an important facility building (educational facility). So this building is included in the seismic design category C. The structural calculation of this building will be planned using the Intermediate Moment Resisting Frame System (SRPMM) method. Building planning refers to building regulations in Indonesia. Earthquake analysis in this planning uses the equivalent static analysis method based on SNI 1726-2012 concerning Procedures for Earthquake Resistance Planning for Building and Non-Building Structures and the 2010 Indonesian Hazard Map with a probability of exceeding 10% in 50 years. The entire structure is reinforced concrete referring to SNI 2847-2019 concerning Structural Concrete Requirements for Buildings, while the structural analysis uses SAP2000 software version 14.0.0 with the results of internal forces for the main beam B1 support moment -435.97 kN / m, field moment 223.72 kN / m and support shear force -278.07 kN, field shear force 278.38 kN. For the main column K1 axial force -2061.16 kN, moment -378.79 kN / m and shear force -168.03 kN. From the results of the structural analysis using the Intermediate Moment Resisting Frame System method, the dimensions of the main beam B1 are 40 x 70 cm with a configuration of 13D19 support flexural reinforcement, 7D19 field flexural reinforcement. and support shear reinforcement D10 - 100 mm and field shear reinforcement D10 - 150 mm. And the main column K1 60 x 60 cm with a flexural reinforcement configuration of 14D19 and shear reinforcement D10 – 150 mm.